Brainstem auditory evoked potentials as the prognostic tool of the functional recovery in children after acute bacterial meningitis - V. B. Voitenkov; A. A. Vilnits; N. V. Skripchenko; S. G. Grigoriev; A. V. Klimkin; A. I. Aksenova (Журнал инфектологии)
Aim of our work was to evaluate the prognostic value of brainstem auditory evoked potentials (BAEPs) for the recovery period outcomes in children with acute bacterial meningitis.Methods. 65 patients with acute bacterial meningitis (average age 3 years, range 3 months-17 years) and 20 healthy controls of comparable age were evaluated with BAEPs. I-V and III-V intervals, amplitudes of the III and V peaks were registered and analyzed. During the recovery period prolonged neurologic observation was performed for the period of 1-6 years. Severe ataxia, pareses, symptomatic epilepsy, speech disturbances and intellectual impairments were regarded as signs of psycho neurologic deficit. ROC-analysis was performed to evaluate sensitivity and specificity of BAEPs parameters in predicting the occurrence of these signs.Results. There were statistically significant difference between the groups on the parameters of I-V interpeak interval and amplitudes of III and V peaks. ROC-analysis revealed that I-III, I-V interpeak intervals and amplitudes of III and V peaks were sensitive and specific in the predicting of the psycho neurologic deficit in the recovery period. Thus, these parameters may be used as a prognostic tool for predicting of such outcomes in acute meningitis in children.